DETERMINANTS OF TAX AVOIDANCE: THE INFLUENCE OF THIN CAPITALIZATION, TRANSFER PRICING AGGRESSIVENESS, AND ACCOUNTING CONSERVATISM WITH FINANCIAL CONSTRAINTS AS A MODERATING VARIABLE - Dodi Irawan; Nensi Yuniarti. Zs; Ummul Khair; Dinal Eka Pertiwi (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
This study analyzes the effect of Thin Capitalization, Transfer Pricing Aggressiveness, and accounting conservatism on tax avoidance, with Financial Constraints as a moderating variable in mining companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2022 period. The research sample was 23 companies from 63 populations, with a purposive sampling method and multiple linear regression analysis and Moderated Regression Analysis (MRA) using SPSS 25. The results show that Thin Capitalization and accounting conservatism have no effect on tax avoidance, while Transfer Pricing Aggressiveness has a significant effect. The moderation test proves that Financial Constraints do not strengthen the relationship between the three independent variables and tax avoidance. This finding confirms that transfer pricing policies are more dominant in influencing tax avoidance practices. Therefore, supervision of affiliated transactions and transfer pricing policies needs to be tightened to suppress the potential for tax avoidance